NILAI-NILAI ISLAM DAN PENGARUHNYA TERHADAP BUDAYA LOKAL - Sajaruddin Sajaruddin (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2022)
This article describes the relationship between culture and religion with a literature review approach. the results of the study understand that the historical journey of reconciliation between Islam as a religion and the local culture that surrounds it and the existence of a legitimative legal basis from syara'. So for the strategy of developing Islamic culture in Indonesia, we need to have a vision for the future. Because culture touches all aspects and dimensions of perspective, attitude to life and its actualization in human life. In addition, cultural movements are more integrative and mass in nature.